An investigation of the incidence of post-traumatic stress disorder, turnover intention and psychological resilience among medical staff in a public hospital in China during the outbreak of the omicron variant in the COVID-19 pandemic in 2022 - Jing, Cui; Feng-Hong, Zhang; Yi-Yan, Wang (Frontiers in Psychiatry, 2022)
[Objective] To analyze the incidence of posttraumatic stress disorder (PTSD) and related factors among medical staff during the COVID-19 pandemic and to provide a basis for adopting relevant psychological interventions to reduce medical staff turnover. [Methods] Using the PTSD Checklist-Civilian Version (PCL-C), the Chinese version of the Turnover Intention Scale (TIS) and the Chinese version of the Connor-Davidson Resilience Scale (CD-RISC), 443 front-line medical staff were invited via the internet to complete a survey. [Results] The incidence of PTSD was 14.4%, the total turnover intention score was 13.38±4.08, and the total psychological resilience score was 87.16±18.42. The prevalence of PTSD was higher among medical staff who were married, had children, and were worried about being infected; in addition, the PTSD group had a higher level of education, higher turnover intention, and lower psychological resilience than the non-PTSD group. The total scores for turnover intention and fear of being infected were risk factors for PTSD, while a high total psychological resilience score and high education level were protective factors for PTSD; the differences were statistically significant (all P<0.05). [Conclusion] PTSD among Chinese medical personnel was associated with marital status, childbirth, education level, turnover intention employment, and psychological resilience.